Chronic kidney disease, cardiovascular disease, and osteoporotic fractures in patients with and without HIV in the US Veteran's Affairs Administration System. (2nd January 2019) - Sutton, S. S.; Magagnoli, J.; Cummings, T. H.; Hardin, J. W.; Edun, B.; Beaubrun, A.
Abstract: Objective: To evaluate the risk of chronic kidney disease (CKD), cardiovascular disease (CVD), and osteoporotic fractures in human immunodeficiency virus (HIV) patients utilizing data within the Veteran's Affairs (VA) Administration system. Methods: A retrospective cohort study utilizing VA system claims (January 2000–December 2016) were extracted from the VA Informatics and Computing Infrastructure (VINCI). Cases included Veterans with an ICD-9/10 for HIV who had at least one prescription for a complete antiretroviral therapy (ART) regimen. Two non-HIV controls were exactly matched on race, sex, month, and year of birth. All patients were followed until the earliest of the following: first incidence of the outcome (identified based on diagnosis codes or laboratory data), last date of VA activity, death, or December 31, 2016. Relative risks (RR) and odds ratios (ORs) were estimated from multivariable Poisson regression models (CVD and osteoporotic fractures) and multivariable logistic regression models (CKD), respectively. Models were adjusted for demographic factors/comorbidities. Results: A total of 79, 578 patients (26, 526 HIV and 53, 052 non-HIV) met all study criteria. The average age was 49.3 years, 38% were black, 32% were white, and 97% were male for both the HIV and control cohorts. The adjusted models demonstrated that HIV was associated with a 78% increased rate of CKD (OR = 1.78, 95% CI = 1.68–1.89), a 32% increased risk of CVD (RR = 1.32, 95% CI = 1.28–1.37), and a 38% increased risk of fractures (RR = 1.38, 95% CI = 1.23–1.56) compared to non-HIV controls. Conclusions: The risk/rate of the three outcomes were significantly higher in HIV patients compared to controls.